Sulfoxidation of pyrimidine thioate derivatives and study their biological activities - Atif A. El-Gharably; A. A. Nassar; N. M. El-Ganzory; Khalil M. Saad-Allah; A. A. El-Barbary (Scientific Reports)
Abstract In a quest to innovate biologically active molecules, the benzoylation of 4,6-dimethylpyrimidine-2-thiol hydrochloride (1) with benzoyl chloride derivatives was employed to produce a series of pyrimidine benzothioate derivatives (2–5). Subsequent sulfoxidation of these derivatives (2–5) using hydrogen peroxide and glacial acetic acid yielded a diverse array of pyrimidine sulfonyl methanone derivatives (6–9). In parallel, the sulfoxidation of pyrimidine sulfonothioates (10–12) yielded sulfonyl sulfonyl pyrimidines (13–15), originating from the condensation of compound 1 with sulfonyl chloride derivatives. The newly synthesized compounds underwent characterization via FT-IR, NMR, mass spectrometry, and elemental analyses. Biological screenings unveiled interesting properties: compounds 1 and 6 exhibited significant antimicrobial potency against S. epidermidis and S. haemolyticus, whereas compound 11 showed distinct insensitivity. Excitingly, compounds 12 and 6 showcased robust antioxidant activity by efficiently scavenging DPPH• radical, underscoring their potential in oxidative stress mitigation. Notably, compounds 10 and 12 displayed promising anti-tumor effects, with compound 12 demonstrating superior efficacy against the MCF-7 breast cancer cell line compared to compound 10. The study revealed a spectrum of biological activities across the synthesized derivatives, with modifications often resulting in diminished bioactivity compared to the parent compound 1. These findings shed light on the intricate relationship between chemical modifications and biological properties, offering valuable insights for future drug discovery endeavors.